Efisiensi Saluran Pemasaran Bunga Pacar Air (Impatiens Balsamina L.) di Desa Dukuh Klopo Kecamatan Peterongan Kabupaten Jombang - Winarti, Winarti; Hartanti, Dyah Ayu Sri; Qomariyah, Siti Nur (Journal of Agricultural Socio-Economics (JASE), 2021)
The purpose of this study is to evaluate the marketing channel for water henna flowers. The marketing margin, the price received by the farmer or farmer's share, profit, and cost all contribute to the henna plant's marketing efficiency. The second purpose is to determine the price transmission elasticity. The study was conducted in the village of Dukuh Klopo, Peterongan District, Jombang Regency. The survey was place between February and April 2021 and included a total of 34 participants: 21 farmers, three collectors, and ten retailers. The survey method was employed for the investigation. Cost analysis, marketing margin and profit, marketing efficiency, and price transmission elasticity are all used in data analysis. In Dukuh Klopo Village, Peterongan District, Jombang Regency, there are two marketing channels for water henna flowers. The first channel comprises of farmers, retailers, and consumers. The second channel consists of farmers, collectors, retailers, and consumers. According to the findings of the research on the efficiency of the water henna flower marketing channel, the second marketing channel is the most efficient, with a value of 0.02 percent.